Strategi Pelayanan Bakmi dan Bubur Ayam Djie Tjap dalam Meningkatkan Kepuasan Tamu - Ni Putu Ayu Friska Damayanti; Kadek Feni Aryati; Ni Luh Gede Liswahyuningsih; Putu Agus Endra Susanta (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The intense competition in the culinary industry in Seminyak, Bali, demands the provision of highquality service to ensure guest satisfaction. Bakmi dan Bubur Ayam Djie Tjap, as the target partner in implementing this Community Service Program, faced several operational challenges: limited staff communication skills, long waiting times, and inconsistent application of Standard Operating Procedures (SOP). This program aims to provide guidance on service strategies and analyze their impact on guest satisfaction. This study employs a qualitative method with a participatory approach conducted in three stages: initial situation analysis, SOP socialization and simulation training, and evaluation through observation, interviews, and online review analysis. The results show a significant improvement in staff communication skills and work behavior. Employees now apply SOP consistently, are more responsive, and act more politely toward guests. These improvements have a positive impact on service quality, as reflected by the increase in the Google Reviews score to 4.7 out of 5. In conclusion, this program is proven effective in improving service quality and guest satisfaction. It is recommended that regular internal evaluations be conducted to maintain the sustainability of service standards.